The Effect of Astaxanthin on Mitochondrial Dynamics in Rat Heart Mitochondria under ISO-Induced Injury - Roman Krestinin; Yulia Baburina; Irina Odinokova; Alexey Kruglov; Linda Sotnikova; Olga Krestinina (MDPI AG, 2023)
Mitochondria are dynamic organelles that produce ATP in the cell and are sensitive to oxidative damage that impairs mitochondrial function in pathological conditions. Mitochondria are involved not only in a healthy heart but also in the development of heart disease. Therefore, attempts should be made to enhance the body's defense response against oxidative stress with the help of various antioxidants in order to decrease mitochondrial damage and reduce mitochondrial dysfunction. Mitochondrial fission and fusion play an important role in the quality control and maintenance of mitochondria. The ketocarotenoid astaxanthin (AX) is an antioxidant able to maintain mitochondrial integrity and prevent oxidative stress. In the present study, we investigated the effect of the protective effect of AX on the functioning of rat heart mitochondria (RHM). Changes in the content of proteins responsible for mitochondrial dynamics, prohibitin 2 (PHB2) as a protein that performs the function of quality control of mitochondrial proteins and participates in the stabilization of mitophagy, and changes in the content of cardiolipin (CL) in rat heart mitochondria after isoproterenol (ISO)-induced damage were examined. AX improved the respiratory control index (RCI), enhanced mitochondrial fusion, and inhibited mitochondrial fission in RHM after ISO injury. Rat heart mitochondria (RHM) were more susceptible to Ca2+-induced mitochondrial permeability pore (mPTP) opening after ISO injection, while AX abolished the effect of ISO. AX is able to perform a protective function in mitochondria, improving their efficiency. Therefore, AX can be considered an important ingredient in the diet for the prevention of cardiovascular disease. Therefore, AX can be examined as an important component of the diet for the prevention of heart disease.